2014
DOI: 10.1116/1.4892172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BCl3 in chlorine-based plasma on etching 4H-SiC for photoconductive semiconductor switch applications

Abstract: Inductively coupled plasma reactive ion etching (ICP-RIE) of n-type SiC epitaxial layers grown on ð000 1Þ 4H-SiC semi-insulating substrates has been investigated using chlorine-based plasma. The etch rate and postetching surface morphology have been studied as functions of the plasma composition, ICP power, RIE power, and process pressure. The authors found that the surface smoothness of the epitaxial layer was increased by introducing BCl 3 into Cl 2 /Ar plasma. An optimized process has been developed yieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…The RF power affecting the plasma flux is called the inductive power ( P ICP ), and the RF power to accelerate the plasma ions, and generate the polarization voltage of the etched material is called RF bias power ( P RIE ). The power delivered from both sources influences the etching rate [ 22 , 28 , 33 ]. Theoretical considerations [ 34 ] showed that regardless of the type of etched material and used working gases, the etching rate in the ICP method is directly related to the self-polarization voltage induced by RF power.…”
Section: The Icp-rie Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The RF power affecting the plasma flux is called the inductive power ( P ICP ), and the RF power to accelerate the plasma ions, and generate the polarization voltage of the etched material is called RF bias power ( P RIE ). The power delivered from both sources influences the etching rate [ 22 , 28 , 33 ]. Theoretical considerations [ 34 ] showed that regardless of the type of etched material and used working gases, the etching rate in the ICP method is directly related to the self-polarization voltage induced by RF power.…”
Section: The Icp-rie Methodsmentioning
confidence: 99%
“…Obtaining the profiles with different wall inclination angles is also possible by the selection of the appropriate composition of the plasma used in the etching process [ 22 , 29 ]. Sung et al [ 23 ] carried out a detailed analysis of the influence of various plasmas (as gas mixtures) on the obtained profiles, for which it was possible to obtain almost vertical walls, with an inclination angle of 87°.…”
Section: Etching Of Sic With Different Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to electron beam irradiation of the samples used in version 3, the doped epitaxial layer was blanket etched to a thickness of 1 µm, after which the doped epitaxial layer remaining between what would become the anode and cathode contacts was completely removed. The etching process used is described in detail in [49]. The region between what would become the anode and cathode contacts was then irradiated with an electron beam with the same parameters as versions 1 and 2; a brass shadow mask was used to prevent irradiation of the anode and cathode regions [50].…”
Section: Versionmentioning
confidence: 99%